CVD SYNTHESIS OF GRAPHENE FROM ACETYLENE CATALYZED BY A REDUCED CuO THIN FILM DEPOSITED ON SiO2 SUBSTRATES - CORTÉS,ANDREA (Sociedad Chilena de Química, 2015)
Few-layer graphene was grown by Chemical Vapor Deposition on a CuO thin film pre-deposited by sputtering on SiO2/Si substrates using acetylene as the carbon source. After evaporation of metal, graphene lies directly in contact with the SiO2 dielectric layer. Raman spectroscopy was used to confirm the presence of a single and/or few-layers of graphene. This procedure does not requiring any post processing to transfer the thin film onto a dielectric substrate or the use of ultra-high vacuum during synthesis.